Community Economic Independence through Menthok Livestock Cultivation: A Case Study of the LAZISNU East Java Productive Zakat Program - Gilang Ramadhani; Atok Syihabuddin (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2026)
Poverty remains a major economic challenge in Indonesia, particularly in East Java, where the poverty rate exceeds the national average. In the context of Islamic economics, zakat is not only a form of worship but also an instrument for poverty alleviation and empowerment. This study aims to analyze the implementation of productive zakat through the duck (menthok) farming program initiated by LAZISNU East Java and its impact on the economic independence of mustahik. Using a qualitative case study approach, data were collected through interviews with program managers, observations, and documentation related to beneficiaries. The findings reveal that the program provides productive assets such as ducks, feed, and cages, accompanied by regular mentoring. This approach enables the ability to develop entrepreneurial skills, increase self-confidence, and generate sustainable income. The choice of menthok farming is considered appropriate due to community familiarity, environmental suitability, and market potential. Although the program is still relatively new, initial results indicate positive behavioral changes and a shift from dependency toward independence. In conclusion, productive zakat programs such as menthok farming have significant potential to empower mustahik economically and gradually transform them into muzakki in the future